2016
DOI: 10.1111/1750-3841.13347
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Metabolic Activity of Listeria monocytogenes on Ready‐to‐Eat Roast Beef Stored at 4 °C

Abstract: Three brands of commercial roast beef were purchased and artificially inoculated with a 5-strain Listeria monocytogenes cocktail at 2 inoculation levels (approximately 3 and 6 Log CFU/g). Although all 3 brands contained sodium diacetate and sodium lactate, inoculated Listeria cocktail survived for 16 d in all 3 brands; significant increases in L. monocytogenes numbers were seen on inoculated Brand B roast beef on days 12 and 16. Numbers of L. monocytogenes increased to 4.14 Log CFU/g for the 3 Log CFU/g inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Differences among the two matrices can be explained by the competition between spiked cells of L. monocytogenes and the microorganisms naturally present on foods. This aspect was already underlined by Broady et al 33 which observed the inability of L . monocytogenes to grow, even if inoculated, in some roast beef samples.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Differences among the two matrices can be explained by the competition between spiked cells of L. monocytogenes and the microorganisms naturally present on foods. This aspect was already underlined by Broady et al 33 which observed the inability of L . monocytogenes to grow, even if inoculated, in some roast beef samples.…”
Section: Resultsmentioning
confidence: 59%
“…To mimic the worst scenario, these cells were used to contaminate 2 different food matrices. The attention was focused on Gorgonzola cheese and sliced roast beef, which can be susceptible to L. monocytogenes colonization 32 , 33 . Both matrices were inoculated with non-treated (control) and treated cells (55 °C and 55 °C TC).…”
Section: Resultsmentioning
confidence: 99%
“…It can grow within a wide temperature range and is resistant to low pH and high salt ( 4 ). This versatility may, at least in part, account for the ability of L. monocytogenes to survive food processing and to grow under conditions routinely used for food preservation ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%